EMPIRICAL INVESTIGATION OF POLICE HARASSMENT OF PRIVATE UNIVERSITY STUDENTS IN OGUN STATE, NIGERIA - Ademolu Oluwaseun Adenuga; Abdullahi Abiodun Oyekanmi (International Studies Journal)
Globally, police is an important institution of established states, given the responsibility to maintain public law and order. However, in Nigeria, these roles have been overshadowed by lack professionalism and civil public engagement which have metamorphosed into undue police harassment of not only the general public, but students of higher institutions. Thus, the study “Empirical investigation of police harassment of private university students in Ogun State, Nigeria’’ is undertaken. The paper is descriptively quantitative in nature with twelve (12) private universities selected in Ogun State as case study. Questionnaires were administered on the respondents and SPSS was deployed for data analysis, while social learning theory was adopted as theoretical framework. The findings of the study revealed that males students in private universities are prone to police harassment than females, that harassment has become police strategy to ease possible extortion of the students and that most cases these harassment were informed by the students bad dresses and hairstyles. The study does recommends for regular in- service training for the police on civil public engagement and respect for citizens inalienable rights; government assertiveness on good character, empathy and obedience to laws as recruitment criteria into Nigeria police; NANS affirmative action against police brutality of students and scaled- up public enlightenment through symposia on mutual respects for the law officers by members of the public.